Broadband power amplifier using hairpin bandpass filter matching network. Issue 4 (1st February 2020) - Haider, Muhammad Furqan; You, Fei; Shi, Weimin; Ahmad, Shakeel; Qi, Tian
Abstract : This Letter presents a new combination of a broadband power amplifier (PA) and an output microstrip hairpin bandpass filter. The filter is designed based on the fifth‐order Chebyshev low‐pass prototype element values. Even–odd mode impedance analysis is used to calculate the filter parameters. Meanwhile, only the fundamental impedance matching is considered for this design. Therefore, a highly selective bandpass response is obtained to provide a spurious‐free fundamental impedance matching. For verification, a broadband PA‐filter component across 1.9–3.1 GHz (48%) is designed and fabricated. Measurements have shown a drain efficiency of 48–56.6% with 39.3–40.5 dBm of maximum output power.